Adrenal hypersensitivy precedes hypercorticism in streptozotocin-induced diabetic mice - Revsin, Yanina (2008)
Previous studies have demonstrated that type 1 diabetes is characterized by hypercorticism and lack of periodicity in adrenal hormone secretion. In the present study, we tested the hypothesis that hypercorticism is initiated by an enhanced release of ACTH leading subsequently to adrenocortical growth and increased output of adrenocortical hormones. To test this hypothesis, we used the streptozotocin (STZ)-induced diabetes mouse model and measured hypothalamic-pituitary-adrenal axis activity at different time points. The results showed that the expected rise in blood glucose levels induced by STZ treatment preceded the surge in corticosterone secretion, which took place 1 d after diabetes onset. Surprisingly, circulating ACTH levels were not increased and even below control levels until 1 d after diabetes onset and remained low until d 11 during hypercorticism. In response to ACTH (but not vasopressin), cultures of adrenal gland cells from 11-d diabetic mice secreted higher amounts of corticosterone than control cells. Real-time quantitative PCR revealed increased expression of melanocortin 2 and melanocortin 5 receptors in the adrenal glands at 2 and 11 d of STZ-induced diabetes. AVP mRNA expression in the paraventricular nucleus of the hypothalamus was increased, whereas hippocampal MR mRNA was decreased in 11-d diabetic animals. GR and CRH mRNAs remained unchanged in hippocampus and paraventricular nucleus of diabetic mice at all time points studied. These results suggest that sensitization of the adrenal glands to ACTH rather than an increase in circulating ACTH level is the primary event leading to hypercorticism in the STZ-induced diabetes mouse model.